2014
DOI: 10.1186/s12861-014-0046-5
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-specific functions of Mud/NuMA mediate binucleation of Drosophilamale accessory gland cells

Abstract: BackgroundIn standard cell division, the cells undergo karyokinesis and then cytokinesis. Some cells, however, such as cardiomyocytes and hepatocytes, can produce binucleate cells by going through mitosis without cytokinesis. This cytokinesis skipping is thought to be due to the inhibition of cytokinesis machinery such as the central spindle or the contractile ring, but the mechanisms regulating it are unclear. We investigated them by characterizing the binucleation event during development of the Drosophila m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 59 publications
2
40
0
Order By: Relevance
“…In this case, genome duplication is uncoupled from daughter cell formation by oscillating G and S phases, as observed in plant trichromes, Drosophila salivary glands, and in many other fly tissues ( Edgar and Orr-Weaver, 2001 ; Hammond and Laird, 1985 ; Swanhart et al, 2005 ). Polyploidy can also result from failed cytokinesis in which cells become binucleate (here on referred to as endomitosis), as observed in megakaryocytes, trophoblasts, hepatocytes, and Drosophila male accessory gland cells and larval tissues ( Cao et al, 2017 ; Gentric and Desdouets, 2014 ; Nguyen and Ravid, 2010 ; Sarto et al, 1982 ; Taniguchi et al, 2014 ). Importantly, endomitosis and endocycling are not mutually exclusive, and both pathways for increasing genome copy number per cell have been found to occur in polyploid cells, for example, in zebrafish epicardium ( Taniguchi et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, genome duplication is uncoupled from daughter cell formation by oscillating G and S phases, as observed in plant trichromes, Drosophila salivary glands, and in many other fly tissues ( Edgar and Orr-Weaver, 2001 ; Hammond and Laird, 1985 ; Swanhart et al, 2005 ). Polyploidy can also result from failed cytokinesis in which cells become binucleate (here on referred to as endomitosis), as observed in megakaryocytes, trophoblasts, hepatocytes, and Drosophila male accessory gland cells and larval tissues ( Cao et al, 2017 ; Gentric and Desdouets, 2014 ; Nguyen and Ravid, 2010 ; Sarto et al, 1982 ; Taniguchi et al, 2014 ). Importantly, endomitosis and endocycling are not mutually exclusive, and both pathways for increasing genome copy number per cell have been found to occur in polyploid cells, for example, in zebrafish epicardium ( Taniguchi et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…As further support for cell-type-specific cytokinetic variation, genomic analysis has revealed that organism-wide mutations in cytokinesis genes are associated with cell-type-specific disruption of cell division in flies, fish, worms, rodents, and even humans ( Bione et al, 1998 ; Moulding et al, 2007 ; Vinciguerra et al, 2010 ; Liljeholm et al, 2013 ; Sgrò et al, 2016 ; Taniguchi et al, 2014 ; Muzzi et al, 2009 ; Giansanti et al, 2004 ; Paw et al, 2003 ; Menon et al, 2014 ; Morita et al, 2005 ; Jackson et al, 2011 ; Di Cunto et al, 2000 ; LoTurco et al, 2003 ; Ackman et al, 2007 ). In human patients, genome-wide association studies have revealed that genomic mutations in cytokinesis genes lead to cell-type-specific division failure and cell- or tissue-type-specific pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…In the Drosophila MAG, binucleation occurs at approximately the midpupal stage (55–60 h after puparium formation at 25°C) by synchronous entry into the last mitotic (M)-phase and subsequent incomplete cytokinesis ( Taniguchi et al 2014 ). On the other hand, in the Cimex MAG, binucleation occurs just before adult molting by synchronous fusion between adjacent cells without synchrony of the cell cycle ( Takeda et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%